Teaching Strategy Preferences Of Novice And Experienced English Teachers In SMPN 1 Sukasada - Komang Diraja Indrarajasa Mahatma Wijana Putra; Luh Putu Artini (Institute of Advanced Knowledge and Science, 2026)
The implementation of the Merdeka Curriculum requires teachers to apply teaching strategies that support student-centered learning and the development of 21st-century skills. This study aimed to investigate and compare the teaching strategy preferences of novice and experienced English teachers at SMPN 1 Sukasada, Buleleng Regency, Bali. A descriptive qualitative design was employed. Data were collected through classroom observations, interviews, teaching strategy checklists, anecdotal notes, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that novice teachers implemented various teaching strategies; however, their use was relatively inconsistent and focused mainly on basic classroom management and content delivery. In contrast, experienced teachers consistently employed social/affective strategies, project-based learning, discovery learning, cooperative learning, and active learning, which promoted greater student participation and interaction. The study also found that teaching experience, student characteristics, learning objectives, teachers’ understanding of instructional strategies, and the availability of learning facilities influenced strategy selection. Overall, experienced teachers demonstrated greater flexibility and effectiveness in implementing teaching strategies aligned with the principles of the Merdeka Curriculum.